2021
DOI: 10.1111/jog.14770
|View full text |Cite
|
Sign up to set email alerts
|

The impact of micronutrient deficiency on pregnancy complications and development origin of health and disease

Abstract: Due to the spread of the western style diet, which is characterized by high intake of processed food, micronutrients (vitamins and minerals) deficiency is increasing in the Japanese population of all ages and genders. During pregnancy, the elevated demand for micronutrients put pregnant women at even higher risk of micronutrients deficiency. Some micronutrients are relatively famous such that women with reproductive age are recommended to take folic acid supplementation for the prevention of neural tube defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Moreover, the elevated demand for micronutrients during pregnancy leads to women being at high risk of vitamin D deficiency and periodontal disease; thus, adequate vitamin D supplementation plays a crucial role in pregnant women to reduce the risk of periodontal disease, and even the risk of PTB and LBW in newborns [ 95 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the elevated demand for micronutrients during pregnancy leads to women being at high risk of vitamin D deficiency and periodontal disease; thus, adequate vitamin D supplementation plays a crucial role in pregnant women to reduce the risk of periodontal disease, and even the risk of PTB and LBW in newborns [ 95 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several micronutrient de ciencies correlate with adverse pregnancy outcomes, including PTB. Pregnant women have a higher demand for micronutrients, and complications can arise from maternal micronutrient de ciency (10).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed evidence of the negative impacts of micronutrient deficiencies during pregnancy in East Africa [ 12 16 ]. To reduce micronutrient deficiency among pregnant women, many national nutrition programs and micronutrient deficiency prevention and control measures have been established [ 17 ].…”
Section: Introductionmentioning
confidence: 99%